Mediated Resistance: The Role of Visual Art in Shaping Identity and Power Discourse in Postmodern Communication - Khofidul A , Muhammad; Firnanda , Deviyan Angel (Professorline, 2025)
This study explores how visual art operates as a medium of mediated resistance in the context of postmodern communication. Drawing on interdisciplinary theories from cultural studies, critical discourse, and media ecology, the research investigates how visual artworks—such as political murals, protest posters, and digital illustrations—challenge dominant ideologies and contribute to the construction of collective identity. Using a qualitative methodology combining semiotic analysis and Visual Discourse Analysis (VDA), the study analyzes selected visual texts to examine their representational strategies, ideological content, and audience interaction. The findings reveal that visual art functions not only as an aesthetic form but as a discursive force that reclaims marginalized narratives, negotiates symbolic power, and activates participatory resistance. This research affirms the role of visual culture as a central arena for the articulation of agency, identity, and alternative worldviews within postmodern media ecologies.